Gendered Pirates: Women’s Roles in Temporary Autonomous Radio - van der Zon, Marian (Women in Radio: Unfiltered Voices from Canada, 2020)
Taking over the airwaves in a small neighbourhood in Montréal was the first step in the creation of the Temporary Autonomous Radio, a pirate station open to women and serving its community when needed. From Montréal, founder Marian van der Zon moved TAR to the West Coast, temporarily on the airways in Victoria, Nanaimo, and rural Vancouver Island. Pirate radio under five watts is usually overlooked in Canada. Beyond music festivals, TAR serves to provide information about issues not often covered in mainstream media. Most importantly, it allows women to be themselves and explore their identities through a non-gendered medium